Gerakan Percepatan Penganekaragaman Konsumsi Pangan (P2KP) Untuk Antisipasi Dampak Perubahan Iklim Pada Sektor Pertanian - Lolita Endang Susilowati; Uyek Malik Yakop; Bambang Hari Kusumo (Jurnal Gema Ngabdi, 2020)
Climate change causes changes in rainfall patterns that is high intensity rain in a short duration. This situation could threaten the agricultural sector which impacts on national food security and food fulfillment for each household. Therefore, it is necessary to introduce an effective strategy to meet household food needs through the P2KP movement in dealing with the threat of climate change. This community service aims to: (1) providing an understanding of climate change and its impact on the food agriculture sector to the community; (2) socializing the "P2KP movement" accompanied by a demonstration plot of the use of house yards for cultivation of vegetables in pots. These community service activities implement a participatory pattern, in which the target community was involved in every decision making both in preparing, implementing, and evaluating the program activities. The results of the community service activities shows that the target community's knowledge of climate change and its impact on the agricultural sector has been successfully improved. The P2KP movement has been socialized and received a positive response from the target community, then they a;ready known to optimizing the use of home yards for cultivation of plants in pots becomes an alternative agricultural system that is resilient in the face of climate change.